Cost-effectiveness of supported self-management for CFS/ME patients in primary care - Richardson, Gerry; Epstein, David; Chew-Graham, Carolyn; Dowrick, Christopher; Bentall, Richard P.; Morriss, Richard K.; Peters, Sarah; Riste, Lisa; Lovell, Karina; Dunn, Graham; Wearden, Alison J. (BioMed Central, 2013)
Background: